2013
DOI: 10.1155/2013/703163
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Positive to Tryptase and c-Kit Receptor Expressing Cells Correlates with Angiogenesis in Gastric Cancer Patients Surgically Treated

Abstract: Background. Angiogenesis is a complex process involved in both growth and progression of several human and animal tumours. Tryptase is a serin protease stored in mast cells granules, which plays a role in tumour angiogenesis. Mast cells (MCs) can release tryptase following c-Kit receptor (c-KitR) activation. Method. In a series of 25 gastric cancer patients with stage T3N2-3M0 (by AJCC for Gastric Cancer 7th Edition), immunohistochemistry and image analysis methods were employed to evaluate in the tumour tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…But the lack of correlation between DMCin and DMVin, demonstrated by this study, may be seen as a sequel of previous studies which have analyzed the mean mast cell density and the mean new vessels density in the gastric wall as a hole, and not on separate, specific areas and depending upon the presence or the absence of Helicobacter pylori infection. Our finding that there are fewer new vessels within the advanced gastric tumors (at least IIB) than in the rest of the stomach wall, correlated with their recognized pro-angiogenic role in the growth and spread of the early stage tumors, as our previous work has demonstrated [3,11], suggests that probably other components of the complex tumoral microenvironment, as well as the rapid growth of advanced tumors, inhibit angiogenesis and limit the density of tumoral new vessels. Low density of tumoral vessels, in contrast with the increased angiogenesis in the rest of the gastric wall is, most probably, another indicator of tumoral aggressiveness, since the tumoral growth is so rapid that exceeds the angiogenesis.…”
Section: Discussionsupporting
confidence: 67%
“…But the lack of correlation between DMCin and DMVin, demonstrated by this study, may be seen as a sequel of previous studies which have analyzed the mean mast cell density and the mean new vessels density in the gastric wall as a hole, and not on separate, specific areas and depending upon the presence or the absence of Helicobacter pylori infection. Our finding that there are fewer new vessels within the advanced gastric tumors (at least IIB) than in the rest of the stomach wall, correlated with their recognized pro-angiogenic role in the growth and spread of the early stage tumors, as our previous work has demonstrated [3,11], suggests that probably other components of the complex tumoral microenvironment, as well as the rapid growth of advanced tumors, inhibit angiogenesis and limit the density of tumoral new vessels. Low density of tumoral vessels, in contrast with the increased angiogenesis in the rest of the gastric wall is, most probably, another indicator of tumoral aggressiveness, since the tumoral growth is so rapid that exceeds the angiogenesis.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have demonstrated that angiogenesis and Ki-67-positive fraction are essential for the development and progression of tumours (27)(28)(29)(30)(31). In addition, numerous studies have suggested that increased tissue MVD and Ki-67 proliferation index, which were individually assessed, were correlated with a poor prognosis in PDACP (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In several tumors such as thyroid, gastric, pancreas, and bladder cancers, and Merkel cell carcinoma TAMCs always appear to be pro‐tumorigenic. Similarly, in several hematologic tumors, such as Hodgkin's and non‐Hodgkin's lymphoma and plasmacytoma mast cells are associated with poor prognosis.…”
Section: Role Of Mast Cells and Basophils In Health And Diseasementioning
confidence: 99%